50 Time critical telephone conversations in the emergency department – a pilot educational project to improve communication skills over the telephone when breaking bad news to relatives. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Edwards, Sarah; Keillor, Lisa; Sandison, Lorna; Millett, Abigail; Davies, Ffion
Abstract : Background: In many countries the COVID-19 pandemic has resulted in unwelcome news being delivered by staff over the telephone as hospital visiting by relatives has been restricted. This includes having to communicate patients have died or are critically unwell. We wanted to increase nursing and medical staff confidence and skills in communicating by telephone, in time critical situations to relatives in the emergency department. Methods: A blended learning package was created. This consisted of a bespoke 15-minute eLearning session and a 1-hour facilitated role-play session. Two simulated telephone calls to a professional actor, posing as the relative were undertaken. The calls simulated realistic time critical telephone conversations including obtaining crucial medical information, conveying news of an acutely unstable patient. A second call to the relative involved breaking the news that the patient had died. Following this the actor gave feedback to the caller focusing on the experience of a relative during these conversations with observers joining as a learning conversation. Group participants reflected on their learning during the session and in a follow up questionnaire. The actors were paid for by the department. Results: 61 staff received this session over the months May and June 2020. Key new elements specific to telephone conversations were explored. During the learning conversation, learners discovered important ideas for framing the conversation, checking the recipient's welfare, and how to open and close the conversations. Conclusion: The unique feedback from the simulated relative's perspective has enabled us to deliver a learning package that helps to prepare learners to deliver unwelcome news over the telephone in time critical situations. Further work will look at the clinical impact of this project.